Clinical Courses of HeartMate II Left Ventricular Assist Device Thrombosis. Issue 2 (February 2020) - Kittipibul, Veraprapas; Xanthopoulos, Andrew; Hurst, Thomas E.; Fukamachi, Kiyotaka; Blackstone, Eugene H.; Soltesz, Edward; Starling, Randall C.
Abstract : We observed different temporal patterns of HeartMate II left ventricular assist device (LVAD) thrombosis regarding clinical manifestations and lactate dehydrogenase (LDH) trends. We propose nomenclature for classification of LVAD thrombosis and compare patient characteristics and outcomes in each pattern of LVAD thrombosis. We reviewed electronic medical records of 362 consecutive HeartMate II devices implanted at Cleveland Clinic from October 2008 to July 2014. We categorized clinical courses of confirmed device thrombosis based on clinical manifestations and LDH patterns. Patients' characteristics, clinical variables, and outcomes were collected for comparison. From a total of 19 confirmed device thromboses, we categorized the patterns of thrombosis into three distinctive types; abrupt thrombosis (Type 1), subacute thrombosis (Type 2), and asymptomatic hemolysis (Type 3). Abrupt thrombosis (Type 1) tended to be the most morbid clinical course with acute-onset thrombosis at 56.5 (interquartile range: 44–71) days, all New York Heart Association functional class III or IV at presentation. Death and need for surgical intervention were not different in each pattern. Asymptomatic hemolysis had unique comorbidities of preexisting cardiac thrombi and preoperative bacteremia. Confirmed LVAD thrombosis has different patterns of clinical presentation and each pattern of thrombosis has unique characteristics and clinical manifestations. Abstract : Supplemental Digital Content is available in the text.